Prevalence of, and risk factors for, HIV, hepatitis B and C infections among men who inject image and performance enhancing drugs: a cross-sectional study. Issue 9 (12th September 2013) - Hope, Vivian D; McVeigh, Jim; Marongiu, Andrea; Evans-Brown, Michael; Smith, Josie; Kimergård, Andreas; Croxford, Sara; Beynon, Caryl M; Parry, John V; Bellis, Mark A; Ncube, Fortune
Abstract : Objective: To describe drug use, sexual risks and the prevalence of blood-borne viral infections among men who inject image and performance enhancing drugs (IPEDs). Design: A voluntary unlinked-anonymous cross-sectional biobehavioural survey. Setting: 19 needle and syringe programmes across England and Wales. Participants: 395 men who had injected IPEDs. Results: Of the participants (median age 28 years), 36% had used IPEDs for <5 years. Anabolic steroids (86%), growth hormone (32%) and human chorionic gonadotropin (16%) were most frequently injected, with 88% injecting intramuscularly and 39% subcutaneously. Two-thirds also used IPEDs orally. Recent psychoactive drug use was common (46% cocaine, 12% amphetamine), 5% had ever injected a psychoactive drug and 9% had shared injecting equipment. 'Viagra/Cialis' was used by 7%, with 89% reporting anal/vaginal sex in the preceding year (20% had 5+ female-partners, 3% male-partners) and 13% always using condoms. Overall, 1.5% had HIV, 9% had antibodies to the hepatitis B core antigen (anti-HBc) and 5% to hepatitis C (anti-HCV). In multivariate analysis, having HIV was associated with: seeking advice from a sexual health clinic; having had an injection site abscess/wound; and having male partners. After excluding those reporting male partners or injecting psychoactive drugs, 0.8% had HIV, 8% anti-HBc and 5% anti-HCV. Only 23% reported uptake of the hepatitis B vaccine, and diagnostic testing uptake was poor (31% for HIV, 22% for hepatitis C). Conclusions: Previous prevalence studies had not found HIV among IPED injectors. HIV prevalence in this, the largest study of blood-borne viruses among IPED injectors, was similar to that among injectors of psychoactive drugs. Findings indicate a need for targeted interventions.